Learning in Networks for Sustainable Development - Lansu, Angelique; Boon, Jo; Sloep, Peter; van Dam-Mieras, Rietje (Proceedings of the International Conference on Networked Learning, 2010)
The didactic model of remote internships described in this study provides the flexibility needed to support networked learners, i.e. to facilitate the development and subsequent assessment of their competences. The heterogeneity of the participants (students, employers, tutors) in the learning network provides relevant diversity in expert perspectives. In today's (networked) business environment, ever more collaboration takes place through virtual platforms and tools. Learning for Sustainable Development could profit from the opportunities such platforms offer, as part of it. Taken from the Brundtland Report (1987), Sustainable Development is development that "meets the needs of the present without compromising the ability of future generations to meet their own needs". Sustainable Development has a high level of complexity, with its need for integration of socio-political, environmental and economic perspectives, its uncertainty in future and its dedication to an enormous range of levels of scale, acting from local to global. Because of the complexity of the concept, the defining of competences and learning outcomes for Sustainable Development is not easy. Learning for Sustainable Development could be described as obtaining the ability to cross the boundaries between multiple perspectives in interaction with stakeholders and actors in sustainability issues. An authentic example on the Dutch-Flemish Scheldt Estuary debate, described in the present study, shows such different perspectives and how they influence the scientific study of and decision-making on sustainability issues. We argue how learners who have to deal with these kinds of different perspectives will develop their personal competences in an effective way. The didactic model of remote internships that we use, allows learners to work in virtual teams on current, authentic research assignments in contact with their customers: real employers in the professional field. Moreover, the didactic model enables learners to define their own activities according to their personal learning goals matching the external requirements of employer and university. This allows our learners - adult distance students at the formal BSc Environmental Sciences programme (Open Universiteit) - to start from their own unique perspectives, having different prior knowledge, in different learning domains and from different professional experiences. The multiple perspectives show themselves in the practice of virtual cooperation with peers and experts from both the academic and professional community. Thus, the present study explores how an online remote internship model can effectively support competence development in a heterogeneous professional learning network.